2021
DOI: 10.1111/ajad.13148
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: The Impact of COVID‐19 on Emergency Department Overdose Diagnoses and County Overdose Deaths

Abstract: Background and Objectives We sought to understand the impact of COVID‐19 on emergency department (ED) overdoses and county coroner verified overdose deaths. Methods Electronic medical health record and county coroner data were gathered and comparisons were made between three 16‐week time periods. In the three time periods, 873 individuals had an overdose diagnosis in the ED and 440 individuals in the county died of drug overdose. Results While total ED patient volume decreased substantially, the number of ED o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 8 publications
(15 reference statements)
0
15
0
Order By: Relevance
“…The pattern of increase agrees with studies of overdose mortality in other regions. 53 , 54 There are distinct pathways by which the pandemic may influence substance use-related mortality, despite the lack of increase in suicide deaths. Unlike suicide, substance use can also serve as a coping mechanism for psychosocial stressors.…”
Section: Discussionmentioning
confidence: 99%
“…The pattern of increase agrees with studies of overdose mortality in other regions. 53 , 54 There are distinct pathways by which the pandemic may influence substance use-related mortality, despite the lack of increase in suicide deaths. Unlike suicide, substance use can also serve as a coping mechanism for psychosocial stressors.…”
Section: Discussionmentioning
confidence: 99%
“…While death totals remained relatively steady between 2017 and 2018, recent estimates place the 2020 national overdose death total at 93,331—an alarming 32% increase from 2019 [ 1 ]. Research indicates that the onset of the pandemic was associated with an increase in overdose deaths nationally [ 2 , 3 ], regionally [ 4 7 ], and locally [ 8 11 ]. The increase in opioid overdose deaths (OODs) during the pandemic has been attributed to various factors: reduced access to interventions, increased levels of stress due to isolation and loss of mental health support, and changes in the types/combinations and purity of drugs and patterns of drug use.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies that conducted comparison between pre-and post-pandemic periods (n=20) showed that overdose death has been increased (n=15 28,29,34,40,65,66,[72][73][74][75][76][77][78][79][80][81] , 7 with significant findings 28,29,65,66,72,73,78 ) compared to pre-pandemic figures. Only a few studies found null (n=3) [82][83][84] or a decrease in overdose death (n=2) 49,85 .…”
Section: Overdose Deathsmentioning
confidence: 99%
“…Seven studies assessed changes in overdose-related death based on sex 65,72,73,75,78,82,87 . Of those, three reported a higher increase in overdose death in men than women 73,75,78 .…”
Section: Inequitiesmentioning
confidence: 99%
See 1 more Smart Citation